Crianças e famílias na educação infantil: pesquisando processos formativos inventivos - Sperandio, Flavia Amorim (2022)
This research discusses the various significances that children and adults conceive about formative processes in their daily experiences. For that, the research tries to understand how parents perceive knowledge production as lived by children and also themselves. Besides, it questions which moments are perceived by parents and caretakers as formative ones, and which inventive formative practices are lived amongst children and adults. The investigation works with the inventive learning approach (KASTRUP, 2007), the discussions about concepts of infancy(ies) and child (SARMENTO, 2008; QVORTRUP, 2010; JENKS, 2002), and the historicity of the concept of family (SCHEINVAR, 2006). The research is situated in a public Early Childhood Education Center, run by the federal government, and had as methodological tools: analysis of records of meetings between parents and school staff, the creation of a group dispositif with children and families (Playfulness Workshop), interviews with families and the production of a research diary. This work analyzes the relations between recognitive politics and adult-centered politics within children-adults relationships; exposes a tension and a dispute of significances between recognition and invention within the scope of formative politics for Early Childhood Education; indicates practices of care and interdependency as ways to increase ‘childness acting’ (VICENTIN, 2016) both in Early Childhood Education and the daily life of children and families.